Plasmodium falciparum GBP2 Is a Telomere-Associated Protein That Binds to G-Quadruplex DNA and RNA - Edwards-Smallbone, James; Jensen, Anders L.; Roberts, Lydia E.; Totañes, Francis Isidore G.; Hart, Sarah R.; Merrick, Catherine J. (Frontiers in Cellular and Infection Microbiology, 2022)
In the early-diverging protozoan parasite Plasmodium, few telomere-binding proteins have been identified and several are unique. Plasmodium telomeres, like those of most eukaryotes, contain guanine-rich repeats that can form G-quadruplex structures. In model systems, quadruplex-binding drugs can disrupt telomere maintenance and some quadruplex-binding drugs are potent anti-plasmodial agents. Therefore, telomere-interacting and quadruplex-interacting proteins may offer new targets for anti-malarial therapy. Here, we report that P. falciparum GBP2 is such a protein. It was identified via ‘Proteomics of Isolated Chromatin fragments’, applied here for the first time in Plasmodium. In vitro, PfGBP2 binds specifically to G-rich telomere repeats in quadruplex form and it can also bind to G-rich RNA. In vivo, PfGBP2 partially colocalises with the known telomeric protein HP1 but is also found in the cytoplasm, probably due to its affinity for RNA. Consistently, its interactome includes numerous RNA-associated proteins. PfGBP2 is evidently a multifunctional DNA/RNA-binding factor in Plasmodium.